Designing, generating, and translating deep-ocean observations for and with international policy makers. (11th August 2022) - Levin, Lisa A; Cimoli, Laura; Gjerde, Kristina; Harden-Davies, Harriet; Heimbach, Patrick; LaScala-Gruenewald, Diana; Pachiadaki, Maria; Pillar, Helen R; Smith, Leslie M; Stocks, Karen; Stopa, Justin E; Wright, Dawn J
Abstract: Deep-ocean observing is essential for informing policy making in the arenas of climate, biodiversity, fisheries, energy and minerals extraction, pollution, hazards, and genetic resources. The Deep Ocean Observing Strategy (DOOS), a UN Ocean Decade endorsed programme, is meeting with representatives from relevant international bodies and agreements to strengthen their interface with the deep-ocean science community, ensure that deep observing is responsive to societal needs, identify points of entry for science in policy making, and to develop relevant products for broad use. DOOS collaboration with the Environmental Systems Research Institute (Esri) facilitates this co-design. A DOOS policy liaison team is being formed to link the contacts, voices, and messaging of multiple deep-ocean networks and organizations in reaching international policy makers. The UN Ocean Decade will help to gain the ear of target communities, scale communication channels appropriately, minimize duplicative efforts, maximize limited resources, and organize inclusive and equitable public and private partners in deep-ocean science and policy.